Comparative Analysis of MOORA and MOOSRA Methods in Determining Prospective Students Recipient of the Indonesian Smart Card (KIP) - Mesran Mesran; Fince Tinus Waruwu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The Smart Indonesia Card (KIP) is a government program breakthrough in equitable distribution of education development throughout the country. The Smart Indonesia Card is here for those who cannot afford to continue their education to a higher level. It is hoped that the existence of the Smart Indonesia Card can create human resources who can compete and innovate in national and international development. In the process of giving the Smart Indonesia Card So far, there are still many problems. To be right on target for Indonesia Smart Card recipients, it is necessary to first consider using a Decision Support System. Comparison of the MOORA and MOOSRA methods in determining prospective students who receive the Smart Indonesia Card with 5 alternatives and 5 criteria. Then the calculation using the MOORA method produces an optimization value of 0.12205 on alternative A2 while sample calculation data using the MOOSRA method produces an optimization value of 1.78948 on alternative A4 as the first rank.